Pemanfaatan Kompos Bulu Ayam untuk Budidaya Selada di Lahan Tailing Pasir Bekas Penambangan Timah - Ismed Inonu; R. Kusmiadi; N. Mauliana (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Inonu, et.al.Â Use of Composted Chicken Feathers for Lettuce Cultivation in Sand Tailings of ex Tin-Mining Site. JLSO 5(2):145-152.Chicken feathers is a solid waste which can be composted for sand tailings of ex tin-mining site ameliorating. The objective of this research was to analysis the Â different doses of composted chicken feathers to obtain the proper dosage for growth and production of lettuce grown on sand tailings of ex tin-mining site. This research used experimental method with Randomized Completely Block Design (RCBD). The treatment factor were doses of composted chicken feathers with five levels (5.0; 7.5; 10; 12.5; 15 tons/ha of chicken feathers) and 20 tons/ha of chicken manure as a control. The results showed Â growth and production of lettuce were treated with 20 tons / ha of chicken manure is higher than all treatment of doses of composted chicken feathers. Sand tailings of ex tin-mining site which is treated 12.55 tons/ha composted chicken feathers produced the highest growth and production of lettuce.